Spring is here, Grumpy bunny! : 2 books in one - Korman, Justine; McQueen, Lucinda (New York, Scholastic, 2008)
Offers a collection of two stories about grumpy Hopper as he is put in charge of a gaggle of energetic baby bunnies who refuse to listen to him and then must hide Easter eggs that he wishes he could have all to himself.